Chilean Guitar Music: Modern Reconstructions of Genre Traditions - Filatova, Tetiana (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
The relevance of the article is to deepen the analytical aspect of knowledge about Chilean guitar music of the second half of the 20th — early 21st centuries in the context of the reconstruction of genre traditions on the example of works by Juan Antonio Sanchez, Gustavo Becerra-Schmidt, Javier Contreras. Main objective of the study is to identify the leading genre traditions of Chilean guitar music and reveal their modern reconstructions in the works of famous authors. The methodology includes methods of historical, cultural, comparative, phenomenological, as well as structural and functional analysis (for a contextual consideration of the creative activities of composers, the study of genre and stylistic elements of the Chilean traditions of folk music, professional-academic and non-academic origin in their influence on European genre models). Results and conclusions. The cultural and historical environment of the formation and development of the Chilean academic guitar repertoire of the second half of the 20th — early 21st centuries is characterized, the links with the performing achievements of domestic virtuosos are determined. The work of composers Juan Antonio Sanchez, Gustavo Becerra-Schmidt, Javier Contreras is considered in the discourse of modern processes of reconstruction of traditions, approbation of innovative methods and techniques of writing of the European avant-garde, use of the resources of American non-academic art. The national genre roots of thematic phenomena have been identified in the process of studying music scores and audio recordings of works, which go back to the primary authentic layers and influence musical vocabulary, creating the foundation of its national identity: Creole cueca, tonada with Iberian origins and hemiole rhythmic archetypes, in particular, in the Sonata for guitar by H. Sanchez; elements of the Araucanian ritual chants of the indigenous Mapuche population in the Fourth Sonata by G. Becerra-Schmidt, as well as the rhythmic formula of the Afro-Brazilian batukada in the finale of the Third Sonata by G. Becerra-Schmidt. It was found that secondary genre and style layers are formed in line with European concert genres: sonatas, concerts, cycles, the compositional and dramatic profile of which changes under the influence of the organic nature of the musical material, its transcultural ethnic ties. Jazz and fusion music-making with elements of the Chilean musical is defined as an equally important genre-style resource. The interferential nature of the inheritance of the authentic cueca tradition through its modern versions created by the legendary Violeta Parra leads to targeted citations, allusions in modern guitar works. Analytically substantiated are the conclusions that thanks to the numerous mosaic carnival contrasts, the abundance of colorful ethno-genre mixtures of Iberian, Indian, African American folklore, to which it is possible to connect the poetics of fusion or experimental percussion techniques of sound production, the originality of the modern Chilean reconstruction of ancient traditions is formed. Such syntheses are due to the internal cultural and historical situation and artistic processes that take place on both sides of the Atlantic.